AR. STRATEGI PENCEGAHAN KORUPSI PEMERINTAH DAERAH GUNA MEWUJUDKAN TATA KELOLA PEMERINTAHAN DAERAH YANG BAIK - Riwanto, Agus; Suryaningsih, Sukarni (Universitas Kristen Satya Wacana, 2024)
This research aims to study and explore the phenomenon of corruption in local government and strategic efforts to prevent it from realizing good local governance. This type of research is socio-legal research with a statutory and conceptual approach and is presented in descriptive-qualitative form. The results of the study show that the factors that cause corruption in the regions are high political costs of regional elections, Regional heads' intervention in the planning of the Regional Expenditure Budget (APBD), regional heads intervene in the management of the APBD, regional heads participate in determining the implementation of permits, regional heads determine the procurement of goods and services, and regional heads buy and sell positions. The strategies to prevent corruption in the regions include reducing the political costs of direct elections, prevention through strengthening internal government supervision, prevention through the performance accountability system of government agencies, prevention through LHKPN reporting and transfer of officials' wealth to the state, and prevention of corruption favoritism.